2021
DOI: 10.1002/adom.202100355
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Dependent Kinetics of Halide Vacancy Filling in Organolead Halide Perovskites

Abstract: halide vacancies/ions is an important factor in the excitonic and charge carrier properties of perovskites. [4g,h] For example, the hole trap-mediated nonradiative charge recombination in CH 3 NH 3 PbI 3 is correlated with the oxidation state of the iodine vacancy. [4h] While an I V − vacancy does not create a hole trap state, a neutral I V vacancy forms a hole trap near the conduction band and accelerates nonradiative charge recombination. Similarly, an I V + vacancy accelerates nonradiative charge recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The long ON-time cutoff is attributed to bromide vacancy filling and decreases in the rates of trapping–de-trapping and charging–discharging. This result is consistent with PL blinking suppression or PL intensity enhancement by halide vacancy filling in MAPbX 3 . ,, For example, Jin et al demonstrated PL blinking suppression in MAPbI 3 NCs doped with Cl . Also, they observed a longer PL lifetime for the Cl-dopped NCs.…”
Section: Resultssupporting
confidence: 76%
“…The long ON-time cutoff is attributed to bromide vacancy filling and decreases in the rates of trapping–de-trapping and charging–discharging. This result is consistent with PL blinking suppression or PL intensity enhancement by halide vacancy filling in MAPbX 3 . ,, For example, Jin et al demonstrated PL blinking suppression in MAPbI 3 NCs doped with Cl . Also, they observed a longer PL lifetime for the Cl-dopped NCs.…”
Section: Resultssupporting
confidence: 76%
“…These results substantiate the passivation of halide vacancy in poorly luminescing PNCs by NaBr treatment, leading to an ensemble-averaged increase in Φ of the sample. Recently, we have reported halide vacancy passivation and PL blinking suppression in MAPbX 3 (X = Br, I) single nano- and microcrystals by supplying the samples with excess MAX in an organic solvent. , Nevertheless, our current work emphasizes the stability and improved PL properties of PNCs in water and other polar solvents.…”
Section: Resultsmentioning
confidence: 86%
“…In the RTC method, the method described in the previous report was modified. [ 31 ] A 1:1 mixture of GBL and 1 m MAPbBr 3 precursor solution was prepared, and 2 µL of this mixture was placed on an ITO‐coated slide glass and left at room temperature for 30 min. After the crystallization of MAPbBr 3 MCs, the surplus solvent was absorbed using filter paper.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, several groups reported perovskite crystallization using N ‐cyclohexyl‐2‐pyrrolidone (CHP) as an additive to control the HP crystal shape. [ 28–32 ] Lee et al. prepared a homogeneous perovskite film using CHP as a morphology‐controlling agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation